Analisis Kebijakan Pelestarian Data Pribadi dalam Pemanfaatan Aplikasi Chatbot Berbasis AI di Indonesia - Gemiharto, Ilham (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2024)
The increasing adoption of AI-based chatbot applications in Indonesia raises concerns about personal data preservation. This qualitative case study investigated the issue through in-depth interviews with chatbot users, developers, and government officials/regulators. This study's findings revealed a gap in user awareness of privacy policies and concerns about data misuse. Developers face challenges balancing personalization with privacy, while regulators acknowledge the need to continuously adapt the legal framework. The study recommends enhancing transparency, user empowerment, and regulatory oversight to ensure the responsible and ethical use of personal data in chatbot interactions.